2018
DOI: 10.1093/gbe/evy105
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and Independent Phases of Transposable Element Amplification in the Genomes of Piciformes (Woodpeckers and Allies)

Abstract: The small and conserved genomes of birds are likely a result of flight-related metabolic constraints. Recombination-driven deletions and minimal transposable element (TE) expansions have led to continually shrinking genomes during evolution of many lineages of volant birds. Despite constraints of genome size in birds, we identified multiple waves of amplification of TEs in Piciformes (woodpeckers, honeyguides, toucans, and barbets). Relative to other bird species’ genomic TE abundance (< 10% of genome), we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 62 publications
5
43
0
Order By: Relevance
“…Two independent waves of CR1 proliferation were detected, with a large proportion of CR1 elements being of relatively young or medium age, as estimated by a molecular clock (Figure 2). These results echo Manthey et al (2018), who also uncovered multiple independent waves of CR1 proliferation across Piciformes. Window analysis of repetitive elements suggested that the distribution of these elements was uneven across the assembly, both within and across scaffolds ( Figure 1C).…”
Section: Genome Annotation Window Analysis and Mutation Rate Estimasupporting
confidence: 75%
See 1 more Smart Citation
“…Two independent waves of CR1 proliferation were detected, with a large proportion of CR1 elements being of relatively young or medium age, as estimated by a molecular clock (Figure 2). These results echo Manthey et al (2018), who also uncovered multiple independent waves of CR1 proliferation across Piciformes. Window analysis of repetitive elements suggested that the distribution of these elements was uneven across the assembly, both within and across scaffolds ( Figure 1C).…”
Section: Genome Annotation Window Analysis and Mutation Rate Estimasupporting
confidence: 75%
“…The paradoxical conjunction of shallow genetic divergence and marked phenotypic differentiation echoes the genomic dynamics of other avian hybrid zones, namely the golden-winged Vermivora chrysoptera and blue-winged Vermivora cyanoptera complex, wherein only a few genomic regions associated with genes that determine plumage color and pattern differentiate the two species (Toews et al 2016). A chromosome-level reference genome for the complex will not only facilitate the identification of the genetic basis of phenotypes (Kratochwil and Meyer 2015), a long-standing goal in evolutionary biology research, but also provide researchers a valuable resource for the examination of emerging fields in genome biology, such as the evolutionary dynamics of transposable element proliferation (Manthey, Moyle, and Boissinot 2018), for which woodpeckers are especially well suited.…”
Section: Introductionmentioning
confidence: 99%
“…Woodpeckers and allies are the exception. Manthey et al [21] demonstrated that TE occurred at higher frequency across several genera of woodpeckers (17-30%), due principally to expansion of CR1 TEs (15-17% of total TEs). Our finding of nearly 22% attributable to CR1 TEs represents a higher proportion of a woodpecker genome than any reported by Manthey et al Because Manthey et al's technical approach likely underestimates TE content, direct comparisons should be considered tentative, but our result does represent the highest CR1 proportion reported for any avian genome.…”
Section: Repetitive Elements In the Assemblymentioning
confidence: 99%
“…More recently, woodpeckers have gained attention for the high amount of repetitive DNA found in their genomes relative to other bird taxa [17][18][19], the result of high levels of genome-wide transposable elements (TEs), which are scarce in most bird genomes [20]. Manthey et al [21] surveyed several woodpecker genomes, and found that TEs make up 17-31% of woodpecker genomes, compared to <10% for other bird species. Increasingly, researchers have suggested that TEs may play a critical role in driving avian evolution [20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Sudden bursts of transposition are common in TEs, and have been documented in a variety of species [4650]. This idiosyncrasy limits direct comparisons between TEs and SNPs, since mutation rates are usually considered constant for the latter.…”
Section: Discussionmentioning
confidence: 99%